Vulnerabilities detection using attack recognition technique in multi-factor authentication - Noor Afiza Mohd Ariffin; Fiza Abdul Rahim; Aziah Asmawi; Zul-Azri Ibrahim (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Authentication is one of the essentials components of information security. It has become one of the most basic security requirements for network communication. Today, there is a necessity for a strong level of authentication to guarantee a significant level of security is being conveyed to the application. As such, it expedites challenging issues on security and efficiency. Security issues such as privacy and data integrity emerge because of the absence of control and authority. In addition, the bigger issue for multi-factor authentication is on the high execution time that leads to overall performance degradation. Most of existing studies related to multi-factor authentication schemes does not detect weaknesses based on user behavior. Most recent research does not look at the efficiency of the system by focusing only on improving the security aspect of authentication. Hence, this research proposes a new multi-factor authentication scheme that can withstand attacks, based on user behavior and maintaining optimum efficiency. Experiments have been conducted to evaluate this scheme. The results of the experiment show that the processing time of the proposed scheme is lower than the processing time of other schemes. This is particularly important after additional security features have been added to the scheme.